Asociación entre el acceso a los Servicios Odontológicos y la altitud en niños menores de 12 años en el Perú, 2019 - Salinas Zevallos, Vanessa Anabeli (2020)
Background: There are different barriers when seeking care in health centers in Peru, altitude is one of them due to poor accessibility, poverty, and altitude problems. Objective: To determine the association between access to dental services and altitude of residence of the children under 12 years of age in Peru, 2019. Materials and methods: The study was cross-sectional with a sample of 42,350 records of children under 12 years of age. The variables were: access to dental care, time of dental care, place of dental care, altitude, region, area of residence, place of residence, natural region, health insurance, wealth index, sex and age. A descriptive and bivariate analysis was performed with the Chi-square test, the results went through a multivariate analysis using the Poisson Regression to obtain the prevalence ratios and adjusted prevalence ratios. There was a 95% confidence level and a p <0.05. Results: It was found that altitude was associated with access to dental care (PR = 1.15; 95% CI: 1.12-1.18; p <0.001), also when the variables area of residence, place of residence, natural region, insurance are considered health, wealth index, sex and age (RPa = 1.10; 95% CI: 1.04 -1.16; p <0.001).